2012
DOI: 10.1093/ndt/gfr628
|View full text |Cite
|
Sign up to set email alerts
|

Fewer pre-emptive renal transplantations and more rejections in immigrant children compared to native Dutch and Belgian children

Abstract: Immigrant children receive fewer pre-emptive and living donor transplantations compared to native children. After transplantation, immigrant children are at higher risk for acute rejection irrespective of the mode of transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…[14] Data from the Netherlands and Belgium demonstrate that the median time to first transplantation after initiation of dialysis in pediatric patients who received a DDKT was 26 months in immigrant children as opposed to 18 months in native children. [7] These disparities mirror findings in the adult literature. [29] Differences in wait time have been largely attributed to differential distribution of HLA genotypes in populations of different racial and ethnic backgrounds.…”
Section: Disparities In Deceased Donor Kidney Transplantation (Ddkt)supporting
confidence: 52%
See 4 more Smart Citations
“…[14] Data from the Netherlands and Belgium demonstrate that the median time to first transplantation after initiation of dialysis in pediatric patients who received a DDKT was 26 months in immigrant children as opposed to 18 months in native children. [7] These disparities mirror findings in the adult literature. [29] Differences in wait time have been largely attributed to differential distribution of HLA genotypes in populations of different racial and ethnic backgrounds.…”
Section: Disparities In Deceased Donor Kidney Transplantation (Ddkt)supporting
confidence: 52%
“…[3] Further, there exist pervasive racial and ethnic disparities in kidney transplantation in both the adult and pediatric setting. [47] While much of the research examining this issue has been conducted in the United States, similar disparities have been identified in Australia[8], Belgium[7], Canada[9] the Netherlands[7], South Africa[10], and the United Kingdom[11] among others, indicating the global nature of this issue. Although it is important to note that some of these disparities may be the result of factors that are beyond the control of the medical system (e.g., co-morbidities and hereditary diseases that are associated with certain ethnic groups), [12, 13] studies have repeatedly demonstrated that differences in medical factors alone are not sufficient to explain the disparities in transplantation in their entirety.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations